Under the Fantasy of Sovereignty: Homonormativity, Relationality and the Potentialities of Queer Sex - Gladney-Hatcher, Caitlin (Atlantis, 2015)
Working with queer, affect, and psychoanalytic theories, this paper conceptualizes sovereignty as an ideal that psychically structures interpersonal relationships as well as individuals’ interactions with institutions. It explores the extent to which homonormativity upholds the ideal of sovereignty in ways that delimit possibilities for relationality and social transformation. It also examines how queerness and queer sex more specifically become sites of resistance which threaten to undo and expose the fantasy of the sovereign self.